Pengaruh Kompensasi dan Faktor Lainnya Terhadap Retensi Karyawan Karyawan PT. X - Moochammad Luthfi Darmawan; Wawa Santoso (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study was to determine the effect of satisfaction, job satisfaction, and career development on employee retention at PT. X. The population in this study are employees of the operational division of PT. X as many as 128 employees. The sampling technique used is purposive sampling, namely sampling with consideration according to the desired criteria. The sample in this study amounted to 107 employees. Data collection techniques using questionnaires and interviews. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis of hypothesis testing data, it shows that the effect has no effect on employee retention, job satisfaction has an effect on employee retention, career development has no effect on employee retention